The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3855/jidc.6812
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of 14-day mortality in multidrug-resistant Acinetobacter baumannii in ventilator-associated pneumonia

Abstract: Introduction: Ventilator-associated pneumonia (VAP) caused by multidrug-resistant Acinetobacter baumannii (MDR-AB) is common in hospitals and impacts patient survival. We determined the incidence of MDR-AB VAP in critical care units and examined the predictors of 14-day mortality in these patients. Methodology: A retrospective case series study was conducted at a tertiary referral teaching hospital in north Jordan. A list of patients with a positive culture of A. baumannii between January 2007 and June 2013 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
12
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
5
12
0
2
Order By: Relevance
“…Spostrzeżenia te pokrywają się z danymi z piśmiennictwa, które wskazują, że u chorych z grup ryzyka, m.in. : poprzednio hospitalizowanych, poddanych wcześniejszej antybiotykoterapii [8], zabiegom operacyjnym, w podeszłym wieku, z przewlekłymi chorobami układu oddechowego, z chorobami układu krążenia, chorobami metabolicznymi, niewydolnością nerek, wątroby, występuje częstsze ryzyko izolacji drobnoustrojów lekoopornych [12,13], a poziom występowania zgonów sięga 61% [5] lub nawet 70% [4]. W niniejszej pracy ustalono, że zastosowane leczenie empiryczne chorych z VAP różniło się od zalecanych rekomendacji.…”
Section: Dyskusjaunclassified
See 1 more Smart Citation
“…Spostrzeżenia te pokrywają się z danymi z piśmiennictwa, które wskazują, że u chorych z grup ryzyka, m.in. : poprzednio hospitalizowanych, poddanych wcześniejszej antybiotykoterapii [8], zabiegom operacyjnym, w podeszłym wieku, z przewlekłymi chorobami układu oddechowego, z chorobami układu krążenia, chorobami metabolicznymi, niewydolnością nerek, wątroby, występuje częstsze ryzyko izolacji drobnoustrojów lekoopornych [12,13], a poziom występowania zgonów sięga 61% [5] lub nawet 70% [4]. W niniejszej pracy ustalono, że zastosowane leczenie empiryczne chorych z VAP różniło się od zalecanych rekomendacji.…”
Section: Dyskusjaunclassified
“…Dodatkowo minimalne wymagania odżywcze, zdolność A. baumannii do długiego przetrwania w środowi-sku szpitalnym oraz naturalna oporność na wiele chemioterapeutyków sprawia, że celem tej bakterii są najczęściej chorzy z obniżoną odpornością. Drobnoustrój ten jest odpowiedzialny za ok. 5-10% przypadków VAP występujących w OIT i wiąże się z wysokim odsetkiem śmiertelności (61%) [5]. …”
unclassified
“…In addition, current limited randomized controlled trials (RCT) have revealed that several medications utilized in childhood pneumonia are signi cantly associated with clinical outcome. For instance, ambroxol, probiotics and bronchodilators are considered as protective factors for mortality in critically ill children [15][16][17][18][19] . Furthermore, Smit et al sedative-hypnotics could signi cantly increase the mortality of children with pneumonia 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Acinetobacter baumannii ( A. baumannii ) has become a major nosocomial pathogen and frequent cause of hospital-acquired pneumonia, surgical wound infections and sepsis ( 1 3 ). The mortality of A. baumannii -VAP cases in critical care units is 42% ( 2 ), rendering A. baumannii a serious threat to ICU populations.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, patients with low immune function are particularly prone to A. baumannii infection, although the reason for this susceptibility remains to be determined. In ICU patients, because of the high prevalence of A. baumannii drug resistance, most A. baumannii infections result in severe bacterial infection, respiratory failure or multiple organ failure, with the mortality rate being equivalent to complex cardiovascular and cerebrovascular diseases ( 2 ). Thus, the constitutive and induced expression of TLR4 in immunocompromised patients with A. baumannii infection is to be investigated.…”
Section: Introductionmentioning
confidence: 99%